Strategic Growth through Corporate Diversification and Restructuring, Mergers and Acquisitions: An empirical Investigation of Rio Tinto’s growth attempts - DU, RUI (2009)
This dissertation is designed for the analysis of Rio Tinto’s mergers and acquisitions cases in 2007-2009. We view the problem from the perspectives of strategic growth in a strategic manner. In order to address the specific problem, we picked up pieces of theories to constitute our literature review. We find that the method of mergers and acquisitions and one company’s growth way are not isolated but in relevance. Undoubtedly, this relationship is clear. It is about what people think (company’s strategic way to grow) and what people do (methods of mergers and acquisitions). Even so, ‘relationship’ is still a less concrete concept. We carefully analyse it by the case studies of Rio Tinto and other qualitative methods. We find this less concrete relationship can be addressed by a series of the concrete qualitative parameters: motives of growth, motives of M&A, managers’ attitudes of diversification and restructuring, macro environment and industrial competition, company’s past growth paths, etc. We also find the M&A is not a universal solution for any firm’s strategic growth. Companies need more complicated co-operation for growing sustainably and reduce the risk at the same time. These findings are not only valid for mining industry but also beneficial for the others.